(untitled) (Journal of Atomic and Molecular Sciences, 2012)
We have performed a detailed study on the synthesis, the characterization of structural phases and superconductivity of the binary FeSe_x system from the Fe-rich phase into the Se-rich phase with 0.80 ≤ x ≤1.20. The results indicate that by long-time low-temperature annealing, single phase sample could be obtained near the composition of FeSe_0.95 with the tetragonal PbO-type structure, while impurities of Fe or Fe_7Se_8 would appear if Fe enriched or Se enriched in the starting composition respectively. Bulk superconductivity was found to exist in highly Se deficient phase, but not the single phase, and superconductivity is very sensitive to the Se vacancy content. The anomalous downturn of resistivity around 100 K was eliminated in Se-rich phase, along with the suppression of the main superconducting phase.